Reproductive performance and growth of N'Dama and Keteku cattle under ranching conditions in the Guinea savannah of Nigeria - Olutogun, O. (1976)
The reproductive performances of N'Dama and Keteku cattle and their crosses in Nigeria-Guinean savannah zone were investigated. Topical discussions on calving distribution, age at first calving, calving interval, production per cow, heterosis in reproductive traits, sex ratio and biological efficiency of productivity, and growth rates; and comparative data on birth weight, weight-forage (WFA) relationships, heterosis in WFA and heritability and expected genetic progress in WFA included.